Relationship of Noise and Individual Characteristics with Blood Pressure of Workers in the Production Area of a Heavy Equipment Component Company in Tegal - Tri Yuliyatin; Siti Dewi Ismayatun (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Noise is any unwanted sound in the work environment that comes from production machines that can cause various health problems. Noise can also cause an increase in blood pressure as a physiological reaction of the body. Apart from the noise factor, an increase in workers' blood pressure can also be triggered by several factors such as worker characteristics (worker’s nutritional status, work experience and work duration). The purpose of this study is to examine whether there is a relationship between noise and worker characteristics and blood pressure. Methods: The design of this study was cross-sectional with a descriptive observational method. The sample in this study was the total population of workers in the company's production area, as many as 42 respondents. Workers' blood pressure was measured before and after work, work environment noise was measured using sound level meter, and questionnaires were used to determine individual characteristics. Results: The increase in blood pressure before and after work occurred most in the unit with the highest noise intensity. The increase in blood pressure before and after work also occurred in the categories of the longest work period and the longest work duration in a day. Conclusion: There was a strong correlation between noise and systolic blood and a weak relationship with diastole. Nutritional status had a weak relationship with blood pressure. Period of work and blood pressure had a moderate relationship, and duration of work and blood pressure had a strong relationship. Keywords: blood pressure, individual characteristics, noise